2015
DOI: 10.1007/s40710-015-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of FAO-56 Penman-Monteith Method for Different Agro-ecological Regions of India

Abstract: This paper analyzes the sensitivity of reference evapotranspiration (ET o ) to climatic variables for different agro-ecological regions of India: semi-arid (Kovilpatti and Parbhani), humid (Mohanpur), and sub-humid (Ludhiana and Ranichauri). The FAO-56 Penman-Monteith (FAO-56 PM) method is used to estimate ET o , and sensitivity of ET o has been studied in terms of change in maximum air temperature (T max ), minimum air temperature (T min ), solar radiation (R s ), average relative humidity (RH avg ), and wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
7
17
0
1
Order By: Relevance
“…The sensitivity analysis showed u 2 and T m to be superior in estimating ET c in hyper-arid environments. This is consistent with the results of a study conducted by Debnath et al (2015). Other parameters also had an insignificant influence on ET c .…”
Section: Calibrated Models Validationsupporting
confidence: 92%
“…The sensitivity analysis showed u 2 and T m to be superior in estimating ET c in hyper-arid environments. This is consistent with the results of a study conducted by Debnath et al (2015). Other parameters also had an insignificant influence on ET c .…”
Section: Calibrated Models Validationsupporting
confidence: 92%
“…In the context of climate change, there is much uncertainty regarding the changes in ET 0 and actual ET as a result of the complex nonlinear relationship between ET and climatic factors. There are large differences among the results obtained in studies that investigated the effects of climatic factors on ET (Debnath et al, ; Estévez et al, ; Nouri et al, ). In China, in terms of ET 0 studies, Wang et al () indicated that a change in wind speed was the main cause of the decrease of ET 0 from 1961 to 2013, followed by the changes in daily maximum temperature (T max ) and sunshine hours.…”
Section: Introductionmentioning
confidence: 99%
“…The use of reanalysis data would enable the calculation of PET through the more accurate combined methods (such as PM). However, the uncertainties associated with reanalysis data should be carefully examined, as some of the modelled variables can display large errors (Reichler and Kim, 2008), and PM has also shown sensitivity to input data inaccuracy (Oudin et al, 2005;Debnath et al, 2015;Estévez et al, 2009;Gong et al, 2006).…”
Section: Further Findings and Future Workmentioning
confidence: 99%